(untitled) (Medico Legal Update, 2021)
Background: Contaminated laparotomy wounds have garnered little attention with high incidence of wound infections. Many techniques have been proposed for their management. The aim of this study is to compare the infection rates of laparotomy wounds using primary closure vs delayed closure in cases of peritonitis. The purpose is to identify a better wound closure technique for their management. Method: This study included 105 patients, who were divided into two groups. Group A underwent primary closure and Group B underwent delayed closure, in which the wound was left open without suturing and saline irrigation was given to be sutured once the wound is clean. The wound infection was assessed using Southampton scoring system. Results: A total of 54 patients, 30 (55.6%) males and 24 (44.4%) females were included. Group A, 27 patients with 55.6% males and 44.4% females. In Group B, 27 patients with 55.5% males and 44.4% females. The mean age in A was 39.4 ± 11.8 while that in B was 37.02 ± 12.5. Group A had an infection .rate of 77.4% whereas Group B had infection rate of only 34%. The duration of hospital stay for Group B was 9.8 and for Group A was 11.7. Conclusions: The delayed closure is an effective technique for wound closure in contaminated wounds, like perforation. Peritonitis, as it reduces wound infection rates and hospital stay